Proposed Mechanisms for Developing the Tax System and Their Impact on Encouraging Investment (A Practical Study in the Iraqi General Commission for Taxes) - Al-Khazaali, Reaah Chfat Abdullah; Ajina, Ayman Al-Nasser (Journal of Ecohumanism, 2024)
The significance of this research stems from the increasing interest in studying the mechanisms for developing the tax system, which play a role in encouraging investment, as well as the effective role that taxes play in economic activities. The tax system encompasses every individual in society according to their capacity and ability, whereby each person contributes to bearing public expenses and burdens based on their income and revenue. This is essential for the state to meet public expenditures and obligations; the wealthy pay more than the poor, and everyone contributes to bearing the burdens resulting from achieving social and economic goals. The tax system works to attract funds, encourage investment, and direct it toward economic and social activities. For instance, exempting agricultural income from taxes has led to directing investment into agriculture, industry, and other sectors. As a result, this creates new job opportunities for citizens, increases local production, and halts or reduces similar goods, thereby providing financial resources for the nation and creating new export opportunities. It also attracts Arab and foreign capital and facilitates the transfer of skills, expertise, and technology in its latest forms.